Induction of Immune Tolerance in Islet Transplantation Using Apoptotic Donor Leukocytes - Naoya Sato (MDPI AG, 2021)
Allogeneic islet transplantation has become an effective treatment option for severe Type 1 diabetes with intractable impaired awareness due to hypoglycemic events. Although current immunosuppressive protocols effectively prevent the acute rejection associated with initial T cell activation in recipients, chronic rejection has remained an obstacle for achieving long-term allogeneic islet engraftment. The development of donor-specific immune tolerance to the allograft is the ultimate goal given its potential ability to overcome chronic rejection and disregard the need for maintenance immunosuppression, which may be toxic to islet grafts. Recently, a breakthrough in tolerance induction during allogeneic islet transplantation using apoptotic donor lymphocytes (ADLs) in a non-human primate model had been reported. Several studies have suggested that the clonal depletion, anergy, and expansion of the antigen-specific regulatory immune network are the mechanisms for donor-specific tolerance with ADLs, which act synergistically to induce robust transplant tolerance. This achievement represents a huge step forward toward the clinical application of immune tolerance induction. We herein summarize the reported operational induction therapies in islet transplantation using the ADLs. Moreover, a few obstacles for the engraftment of transplanted islets, such as islet immunogenicity and instant blood-mediated response, which need to be resolved in the future, are also discussed.